Foreign Body in the Esophagus: A Retrospective Study from National City Hospital, Bharatpur, Chitwan, Nepal - Shrestha, Barun; Nepal, Choodamani (Journal of National Heart and Lung Society Nepal, 2025)
Foreign body (FB) ingestion is a common clinical emergency requiring prompt diagnosis and management. This retrospective study analyzes demographic distribution, types of ingested foreign bodies, and sites of impaction among 85 presented in National City Hospital, Bharatpur, Chitwan, Nepal during the period of one year from January 2024 to December 2024. The majority of cases occurred in adults, with meat bones being the most common foreign body. Most FBs were lodged in the upper esophagus, and endoscopic retrieval was the primary management approach. This study highlights the seasonal variation in foreign body ingestion, particularly during Nepalese festivals when meat consumption increases.